Modular structure, local flexibility and cold-activity of a novel chitobiase from a psychrophilic Antarctic bacterium - Lonhienne, T; Zoidakis, J; Vorgias, CE; Feller, G; Gerday, C; and Bouriotis, V (2001)
The gene archb encoding for the cell-bound chitobiase from the Antarctic Gram-positive bacterium Arthrobacter sp. TAD20 was cloned and expressed in Escherichia coli in a soluble form. The mature chitobiase ArChb possesses four functionally independent domains. a catalytic domain stabilized by Ca2+, a,galactose-binding domain and an immunoglobulin-like domain followed by a cell-wall anchorage signal, typical of cell-surface proteins from Gram-positive bacteria. Binding of saccharides was analyzed by differential scanning calorimetry, allowing to distinguish unequivocally the catalytic domain from the galactose-binding domain and to study binding specificities. The results su,,est that ArChb could play a role in bacterium attachment to natural hosts. Kinetic parameters of ArChb demonstrate perfect adaptation to catalysis at low temperatures, as shown by a low activation energy associated with unusually low K-m and high k(cat) values. Thermodependence of these parameters indicates that discrete amino acid substitutions in the catalytic center have optimized the thermodynamic properties of weak interactions involved in substrate binding at low temperatures. Microcalorimetry also reveals that heat-lability, a general trait of psychrophilic enzymes, only affects the active site domain of ArChb. (C) 2001 Academic Press.